Herbal Remedies in Cosmeceuticals Formulation: A Review on Nepalese Perspectives - Gyawali, Rajendra; Narayan Paudel, Prem (Annapurna Journal of Health Sciences, 2023)
Introduction: The beauty product preparation from natural ingredients reaches is historical. People of rural area where the practice of modern cosmetic products are not accessible, they mostly use and depend upon the locally available ingredients in their own formulations. The inclusion of extracts in topical formulations can minimize the skin damage of oxidative stress, which has been associated with delaying the aging process. Therapeutic benefits by addition of plant-based active ingredients such as alpha-hydroxy acid, retinoic acid, ferulic acid, ascorbic acid, and coenzyme Q10 are common. Natural preservatives are also in priority but it is equally important to carry research for their efficacy and assurance.Methods: An independent approach was used to conduct the literature review. Major well-known bibliometric information sources studied are the Web of Science, Scopus, Mendeley and Google Scholar. Several keywords like name of plants, skin whitening, anti-acne, herbal cosmetics, Ayurvedic herbs, skin cancer, moisturizer etc were chosen to obtain a large range of papers to be analyzed. Local news papers, research reports and official websites were also studied.Results: The results obtained from this review showed that, there are numerous herbs which are effective and safe for cosmetic purpose. Herbal based cosmetic factories are started in Nepal but their research part not much strong and found frequently lead by non-pharmacist or non-chemist human resources. Herbs are rich in vitamins, phenolics and carotenoids which have mainly anti-aging, revitalizing and rejuvenating properties. Herbs have vitamins, saponins and flavanoids which supply various nutrients to hair and help to darkening of hair. Different literatures available prove that the heavy metals are also mixed in large quantity in cosmetics found in Nepalese market. There is an immediate need to execute strong guidelines regarding the quality of cosmetic products in Nepal.Conclusions: The current review on herbal cosmetics focuses on the natural sources of cosmetics, their medicinal benefits, mechanism of action, key chemical constituents and their advantages along with safety.